The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1159/000525262
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MRI in the Treatment of Drug-Resistant Focal Epilepsy

Abstract: <b><i>Background:</i></b> Epilepsy is a prevalent chronic condition affecting about 50 million people worldwide. A third of patients with focal epilepsy suffer from seizures unresponsive to medication. Uncontrolled seizures damage the brain, are associated with cognitive decline, and have negative impact on well-being. For these patients, the surgical resection of the brain region that gives rise to seizures is the most effective treatment. <b><i>Summary:</i></b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 79 publications
2
15
0
Order By: Relevance
“…This rate is in line with previous data 6,10,33 . Many patients have subtle lesions that might be undetected on routine MRI but have an histopathological correlation 9,33 . The crucial need to detect surgically amenable lesions in patients with focal epilepsy has motivated the development of sophisticated detection methods 27,34–36 .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This rate is in line with previous data 6,10,33 . Many patients have subtle lesions that might be undetected on routine MRI but have an histopathological correlation 9,33 . The crucial need to detect surgically amenable lesions in patients with focal epilepsy has motivated the development of sophisticated detection methods 27,34–36 .…”
Section: Discussionsupporting
confidence: 86%
“…In 2002, von Oertzen and colleagues 11 pointed that the application of an epilepsytailored MRI protocol plus an expert neuroradiologist reading resulted in a failure rate significantly lower than a "standard" MRI and nonexperts reports (9% in the former situation versus 61% in the latter). Similar conclusions were reported later 8,9,18 and different time-effective epilepsy-MRI protocol for drug-resistant epilepsy have been published so far. [11][12][13]18,19 A recent systematic review and meta-analysis demonstrated that a dedicated MRI protocol benefits the detection rate in epilepsy surgery candidates, particularly for FCD.…”
Section: Harness Protocolsupporting
confidence: 89%
See 3 more Smart Citations